Aleksandr Konstantinovich Matveev. An Onomatologist and Researcher of Ancient Language Contacts - Matveeva, Tamara; Lukianin, Valentin (Quaestio Rossica, 2015)
The article considers the personality and research activity of Aleksandr Konstantinovich Matveev (1926–2010), an outstanding Russian linguist, corresponding member of the Russian Academy of Sciences and professor of Ural State University (presently, Ural Federal University). Specializing in the study of proper names (onomatology), Professor Matveev argued that the class of geographical names was crucial for the reconstruction of ethno-historical data on the former distribution of tribes and peoples in the vast territories of present-day Russia. Among his achievements is the development of principles and methods of onomastic research based on field material collected by means of frontal survey. With the view of collecting linguistic material, A. K. Matveev established the Toponymic Expedition of Ural University that explored a number of northern regions of European Russia as well as the Northern and Middle Urals. During a 50-year period, the expedition collected millions on onomastic and lexical units. The unique card files stored at the department established by him at Ural Federal University are used as a basis for theses and other research as well as dictionaries, and they are used to correct cartographic data. The central issue of the scholar’s research was that of substrate in Russian toponymy. Together with his acolytes and colleagues, he searched for Finno-Ugric (Chud) and Merya language heritage in the Russian North, and Mansi loan words in the Northern Urals. The research material was analyzed with the help of a complex of methods (i. e. interlingual phonetic and other comparisons, the linguo-geographic method of cartographing and comparisons with data provided by related disciplines). Professor Matveev’s findings and the find ings of the Ural Toponymic Research School appear in onomastic and lexical dictionaries. The final conclusions of their toponymic research go far beyond linguistics and have a historico-ethnic character. Professor Matveev is an eminent figure who evokes the memories of world-famous linguists-travellers of the past. He combines the audacity of a discoverer, the rigor of a scholar—including excellent organizing skills—the spirit of a zealous protector of his homeland’s spiritual culture and the talent of a teacher. People were drawn to him by his vast erudition and versatile interests, and his humaneness combined with devotion to his research interests. A. K. Matveev’s Research School and the Toponymic Expedition continue their intensive work until the present day.